2001
DOI: 10.1203/00006450-200102000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Interconversions in the Fetal-Placental Unit: The Animal Model and Human Studies In Vivo

Abstract: Fetal growth and development are dependent upon the adequate provision of oxygen and substrates from the maternal circulation. The need for amino acids is related to protein synthesis, interconversion to other substrates, and oxidation. Amino acids cross the placenta by active transport systems, and their concentrations in the fetus are higher than in the mother. In addition, most amino acids are extensively metabolized within the placenta, and, for some nonessential amino acids, placental synthesis has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 38 publications
2
45
0
2
Order By: Relevance
“…The placenta concentrates folate in the intervillous space (Guigliani et al 1985a, 1985b, Cetin 2001, Camelo et al 2004. Folate receptors accumulate 5-CH 3 THF, the principal circulating form of folate, at the brush border of the syncytiotrophoblast and mediate the transport of folate compounds into the syncytiotrophoblast by endocytosis (Suh et al 2001, Van der Put et al 2001, Solanky et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta concentrates folate in the intervillous space (Guigliani et al 1985a, 1985b, Cetin 2001, Camelo et al 2004. Folate receptors accumulate 5-CH 3 THF, the principal circulating form of folate, at the brush border of the syncytiotrophoblast and mediate the transport of folate compounds into the syncytiotrophoblast by endocytosis (Suh et al 2001, Van der Put et al 2001, Solanky et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Human in vivo studies with stable isotopes have shown delivery of neutral amino acids to the fetus in normal pregnancy is only just sufficient to meet requirements (Cetin, 2001), and in FGR maternofetal 13 C-leucine transfer is reduced (Marconi et al, 1999). Such findings provide the rationale for studying placental amino acid transport systems in relation to FGR.…”
Section: Placental System a And Fetal Growth Restrictionmentioning
confidence: 99%
“…During the second half of gestation, increasing placental surface area does not match the increase in fetal size, therefore increasing amino acid transporter abundance and capacity is necessary for appropriate fetal growth. In addition, in vivo human and sheep studies have shown that many amino acids transferred to the fetus are produced in the placenta through interconversion of metabolically related amino acids [111,112].…”
Section: Placental Amino Acid Transfer and Metabolismmentioning
confidence: 99%
“…The development of techniques using isotope tracers has allowed the study of the bidirectional flow of amino acids and has improved the understanding of placental transport and metabolism of amino acids [107,[112][113][114][115]. In the human placenta, the fetal endothelial and syncytiotrophoblast layers are the only two cell layers separating maternal blood from fetal blood.…”
Section: Placental Amino Acid Transfer and Metabolismmentioning
confidence: 99%